Gendered impacts of the 2007-08 food price crisis: Evidence using panel data from rural Ethiopia - Kumar, Neha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2011)
This paper provides empirical evidence on the gendered impact of the 2007-08 food price crisis using panel data on 1,400 households from rural Ethiopia that were initially surveyed before the onset of the crisis, in 1994-95, 1997, and 2004, and after food prices spiked, in 2009. It investigates whether female-headed households are more likely to report experiencing a food price shock, and whether female-headed households experiencing a shock are more (or less) likely to adopt certain coping strategies, controlling for individual, household, and community characteristics. Our findings suggest that female-headed households are more vulnerable to food price changes and are more likely to have experienced a food price shock in 2007-08. Because female-headed households are also resource poor and have a larger food gap compared with male-headed households, they cope by cutting back on the number of meals they provide their households during good months and eating less preferred foods in general. Our findings that land—particularly better quality land—has a protective effect against food price shocks also highlight the role of strengthening land rights of the poor, particularly poor women, to enable them to cope better with food price increases.